Pengaruh surfaktan nonionik yang dicampurkan dalam basis salep hidrofil (usp) terhadap pelepasan asam salisilat secara in vitro=The Influence of Nonionic Surfactans Mixed into Hydrofile BaskZalf to the Release of Salicy - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
This study aims to find out the effect of the use of nonionic surfactants Brij 35, 99, 30 and 93 with the concentration of 0.1%, 1%, 3%, 5% and 7% instead of sodium lauryl sulfate on the rate of release of salicylic acid with 5% concentration. The rate of release of active substance was computed using Higuchi's law as a function of square root of time. The influence of concentration and ELB and their combination were counted using analysis of variance, t-test and Scheffe and p = 0.05. The result shows optimum release of salicylic acid is obtained when the concentration of surfactants is 1%. Compared with the use of sodium lauryl sulfate, the use of Brij 30, 99 and 35 respectively increased the release of medicament 1.26 times, 1.43 and 1.48 times. The 0/W type and MB increase the rate of release of salicylic acid The higher the HLB, the faster the rate of release.